(3efXheI aj GdEQKs - (3Ydj GdbRhjfjs ((3HNW GdeDdas)
(3ChdgG (B:s
(3GdMeO ddg Ydi eG aQVG (B*** (3ddQMe GdejQGK eeG GaJQVG (B... (3HGdfSH GdEQK ddChdhjI (B*** (3hGdaQV hGdhdGA hGdRhLjIs
(3BNQgG (B:s
(3BNQgG(B: (3jONd aj GdCMcGe cGdEQK heG (B*** (3TGcdg aKQ EQK fXeGs
(3jdjgG efXheI aj VQH GdCYOGO, (B2 (3hQbI (B(36- 39)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L(B24: 24s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis